Low Level Antibodies Against Alpha-Tropomyosin Are Associated With Increased Risk of Coronary Heart Disease - Zhang, Yin; Zhao, Heru; Liu, Bin; Li, Li; Zhang, Lulu; Bao, Mei; Ji, Xinyu; He, Xiaojuan; Yi, Jianfeng; Chen, Peng; Lu, Cheng; Lu, Aiping (Frontiers in Pharmacology, 2020)
Objective Natural autoantibodies have been implicated to play a key role in the pathogenesis of coronary heart disease (CHD) because they augment autoimmune activation. The aim of this study was to identify novel specific autoantibodies of CHD, and analyse the relationship between their levels and CHD risk indicators. Approach and Results First, clinical data and sera from CHD patients were collected. Then, one protein microarray containing 37 proteins that represent candidate autoantigens was developed. The arrays were used to profile autoantibodies in randomly selected sera from 35 samples (20 CHD patients, and 15 healthy controls). After that, microarray data were analysed and autoantibodies for CHD were screened out. Then, ELISA detection was conducted to validate the differentiable autoantibodies using larger numbers of serum samples (131 CHD patients, and 131 healthy controls). Finally, the associations of antibodies with CHD risk indicator parameters were assessed. Inter-group comparison by microarray indicated that three CHD novel autoantibodies, including glucose-6-phosphate isomerase (G6PI), alpha-tropomyosin (TPM1), and heterogeneous nuclear ribonucleoprotein D-like (HnRNPDL), were significantly (P<0.05) increased when compared with the healthy controls. Moreover, a significant increase of IgG autoantibodies for these three autoantigens was confirmed in CHD patients by ELISA (P<0.0001). The correction analysis revealed a negative correlation of anti-TPM1 antibody levels and total cholesterol (TC) (P=0.0034), and low-density lipoprotein cholesterol (LDL) (P=0.0086), respectively. Conclusions G6PI, TPM1 and HnRNPDL were CHD natural autoantigens, and serum anti-TPM1 antibody could be used as a potential marker to predict the risk for CHD patients.